2009
DOI: 10.29333/ejgm/82679
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Soft Tissue Chondroma and Periosteal Chondroma of Thumb

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In approximately 20% of the patients, the lesion is painful and tender, as in our cases, especially if located in the planter aspect of the foot [5] [15] [16]. Almost all of these tumors are solitary, but Dellon et al [17] [18], reported bilateral chondromas in the right index and left ring fingers in a patient with renal failure. Multiple extraosseous chondromas are more likely examples of synovial chondromatosis.…”
Section: Discussionmentioning
confidence: 61%
“…In approximately 20% of the patients, the lesion is painful and tender, as in our cases, especially if located in the planter aspect of the foot [5] [15] [16]. Almost all of these tumors are solitary, but Dellon et al [17] [18], reported bilateral chondromas in the right index and left ring fingers in a patient with renal failure. Multiple extraosseous chondromas are more likely examples of synovial chondromatosis.…”
Section: Discussionmentioning
confidence: 61%
“…The CARNEY Triad associates a pulmonary chondroma, a gastric leiomyosarcoma and, an extra-surrenial paraganglioma [10]. On the clinical level, it is a painless swelling of the soft parts slowly increasing in volume so that the patient does not immediately seeks medical advice [11, 12]. On the radiological level, the appearance of the extra-osseous chondroma varies according to the size of the calcification of the tumor center and the reaction of the adjacent tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically it is slowly growing usually painless small single or multiple nodules smooth to irregular lobulated soft tissue mass and often ignored by the patients. One case of bilateral chondroma was reported by Dellon et al in left ring and right fingers with renal failure 6,7 . In our presenting case it was slowly growing for three years and presented to clinician due to occasional pain.…”
Section: Introductionmentioning
confidence: 98%